2021
DOI: 10.2320/matertrans.mt-m2021031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vanadium Contents on Microstructure and Mechanical Properties of Ti–6Al–xV Components Produced by Wire + Arc Additive Manufacturing

Abstract: Wire + Arc Additive Manufacturing (WAAM) is an advanced manufacturing technology by inexpensive Gas Tungsten Arc Welding (GTAW) technology. Key microstructural features of the as-built WAAM alloy include large columnar ¢ grains, grain boundary ¡ colonies, and Heat Affected Zone (HAZ) banding, which generally leads to low ductility and anisotropy. In this study, Ti6AlxV (x = 0, 2, 4) alloys were prepared by WAAM, the effects of vanadium content on the microstructure, tensile properties and impact toughness were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In either case, due to the low Ti64 inclusions in the welding seam, the concentration of V is significantly lower compared to that of the base Ti64 alloy. Zhang et al [32] studied the effect of the vanadium content on the structure and mechanical properties of wire arc additively manufactured Ti-6Al-xV specimens. They reported that an increase in the V content resulted in a decrease in the size of the lamellar αTi structure.…”
Section: Resultsmentioning
confidence: 99%
“…In either case, due to the low Ti64 inclusions in the welding seam, the concentration of V is significantly lower compared to that of the base Ti64 alloy. Zhang et al [32] studied the effect of the vanadium content on the structure and mechanical properties of wire arc additively manufactured Ti-6Al-xV specimens. They reported that an increase in the V content resulted in a decrease in the size of the lamellar αTi structure.…”
Section: Resultsmentioning
confidence: 99%
“…An et al. [37] researched the effects of vanadium content on the microstructure, tensile properties, and impact toughness of Ti–6Al–xV components produced by WAAM. It was reported that a monotonic increase in yield strength and ultimate tensile strength was observed with the increase of vanadium content while the fracture strain and impact toughness changed in the opposite trend.…”
Section: Recent Aluminium Alloys Manufactured Using Waammentioning
confidence: 99%